Just War Determination through Human Acts Valuation: An Igbo-African Experience - Ezebuiro, Anthony Udoka; Ejim, Emeka Simon; Uke, Innocent Anthony (Conatus - Journal of Philosophy, 2024)
This paper analytically reflects and x-rays the African perspective of just war using human act valuation as the basis of argument. In the wake of time, philosophers, psychologists and ethicists have differentiated between two kinds of actions, namely human action and action of man. Accordingly, man is convinced that he is different from the rest of the animal family; hence he acts at a level which dogs, for example, cannot attain. In any case, man does not always act as a man; his activity is not always stamped by what distinguishes him from other beings, namely rationality. Sometimes, he acts at the level he shares with other living beings; in other words, his activity at this level is ruled by a natural necessity or determined in the sense that doings at this sphere are not called actions, for they are ‘instinctive, thoughtless movement, mannerisms, reflex actions, or what is done under the influence of psychic constraints, hypnotic suggestions or demented frenzy etc.’ Such actions are rightly called actions of a human being, since their source is that bodily and spiritual individual who is called Peter, Paul, etc., but they are not human actions per se. They do not express the individual being; they do not proceed from him precisely as a human being. The only genuinely human action is the one which a human being performs in virtue of what distinguishes him from other beings. Since this is nothing other than reason, or rather, rationality, human actions are the actions which are performed when he acts as a rational being. Therefore, human acts are those actions of man that have their source in man’s rationality or spirituality, understood in terms of human’s interiority from which his activities flow. Beyond this, the African has got another sense of human act valuation, which is community-based or community-centered. In line with this, an attempt is made here to demonstrate how just war can be determined through human act valuation using the Igbo-African perspective as a case study.